A study on validation of moment-curvature relationship of lime sludge-based blended cement concrete on numerical modeling (ATENA). (November 2022) - Praveen Kumar, V.V.; Prasad, E.V.
Abstract: It is evident that the deformation capacity of any RCC structure is always very significant in the flexural design, other than the compressive strength aspect. When a structure is fully-loaded, adequate deformation capacity available in the structure can ensure safety. The present study focused on the flexural behavior of RCC beams consisting of industrial by-products from the paper industry known as lime sludge. The parameters considered in the present study include the strength of control mix concrete (30 MPa, 50 MPa, and 70 MPa), the combination of mineral admixtures (fly ash, silica fume, and lime sludge) as a partial replacement of cement in the preparation of blended concrete mix and type of reinforced section (under-reinforced and over-reinforced beams). Beams of size 1800 mm × 100 mm × 200 mm were cast and tested for flexural strength and the moment-curvature relationships. The improvement in the moment carrying capacity of under and over-reinforced RCC beams was noticed to be 40.12 %, 30.64 %, 22.98 %, 34.80 %, 30.13 %, and 19.44 % in 30 MPa, 50 MPa, and 70 MPa concrete respectively. The curvature of under and over-reinforced concrete RCC beams has improved by 7.64 %, 7.58 %, 7.44 %, 10.30 %, 7.30 %, and 5.15 % in 30 MPa, 50 MPa, and 70 MPa concrete respectively. Validation of the experimental M-ϕ relationship was obtained through the numerical model using FEM-based software ATENA. The experimental results of the moment-curvature relationship are in good agreement with the numerical model.